Pengaruh Latihan Ladder Ickey Suffle Dan Quick Feet Dengan Interval 1:3 Dan 1:5 Terhadap Peningkatan Kecepatan Dan Kelincahan - Finsensius Mbabho (Jayapangus Press, 2021)
This research is intended to (1) analyze effect of Ickey Shuffle and Quick Feet Ladder by using the method of interval training in 1:3; (2) analyze the effect of Ladder Ickey Shuffle and Quick Feet Ladder by using the method of interval training in intervals 1:3 and 1:5towards the increasing of speed and agility; (3) analyze the differences between ickey shuffle exercise group and quick feetby using the method of interval training in 1:5 intervals 1:3 and 1:5towards the Improvement of Speed and Agility. This research is a quantitative research by using quasi-experiental with factorial design. In analyzing the data, it uses T-Test paired test and MANOVA. The result of the research shows that all of experiment groups have increasing in speed and agility significantly. It is known by the result of T-Test that shows that significant value of all of experiment groups are less than 0, 05. While the result of multivariate test show that the exercise of ladder ickey shuffle with interval 1:3 more experience significantly towards agility, meanwhile ladder quick feet exercise with interval 1:3 more influence significantly towards speed. Based on the above analysis, it can be concluded that there is an increased speed and agility for each experimental group after the training given ickey shufle and quick feet seen from the results of t-test. In addition there are differences in the effect through MANOVA test, and training programs ickey shuffle is more effective than training quick feet to increase agility; quick feet more effective than training ickey shuffle to increase speed